"The enchantment of property": Arthur Young, enclosure, and the cottage economy in England, 1770–1840. (1st August 2019) - Handy, Jim
Abstract: English agricultural practice changed dramatically in the late 18th and early 19th centuries as enclosure, the dominance of commercial short‐term leases for tenant farmers, and the proletarianization of the agricultural labour force completed what has been called an agricultural revolution. A less often noted aspect of this change was what was called "a war on cottages" and cottage gardens. The Board of Agriculture and Arthur Young were important cheerleaders for this process. Yet many of the most prominent members of the Board of Agriculture made impassioned appeals for the provision of land for English cottagers as a way to reduce poverty and stressed that cottagers produced remarkable returns from their small farms. Arthur Young became the most vocal proponent of land for cottagers. This article suggests that their appeals for land for cottagers were limited by both farmers' desire for easily controlled labour and misplaced concerns about the supposed inevitability of the poverty inherent in very small farms.